2008
DOI: 10.1110/ps.035881.108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and mutagenic analysis of GDOsp, a gentisate 1,2‐dioxygenase from Silicibacter Pomeroyi

Abstract: Dioxygenases catalyze dioxygen incorporation into various organic compounds and play a key role in the complex degradation pathway of mono-and polycyclic aromatic and hetero-aromatic compounds. Here we report the crystal structure of gentisate 1,2-dioxygenase from Silicibacter pomeroyi (GDOsp) at a 2.8 Å resolution. The enzyme possessed a conserved three-dimensional structure of the bicupin family, forming a homotetramerization. However, each subunit of GDOsp unusually contained two ferrous centers that were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 37 publications
(49 reference statements)
1
52
0
Order By: Relevance
“…Salicylate is not converted but acts as a competitive inhibitor (55,56). All GDOs characterized to date belong to the bicupin family (1,20). Each bicupin subunit of the homotetrameric enzyme from Escherichia coli contains a mononuclear iron center coordinated to three His ligands, leaving three solvent-occupied sites on the iron available for interactions with substrate (1).…”
Section: Gentisate 12-dioxygenase and Related Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salicylate is not converted but acts as a competitive inhibitor (55,56). All GDOs characterized to date belong to the bicupin family (1,20). Each bicupin subunit of the homotetrameric enzyme from Escherichia coli contains a mononuclear iron center coordinated to three His ligands, leaving three solvent-occupied sites on the iron available for interactions with substrate (1).…”
Section: Gentisate 12-dioxygenase and Related Enzymesmentioning
confidence: 99%
“…Cleavage of the O-O bond and insertion of one oxygen atom into the ring, promoted by ketonization of the hydroxyl substituent at C-5, would generate a cyclic lactone that may be hydrolyzed by the hydroxide that after O 2 cleavage remained at the iron (1,20,56). The mechanism proposed for GDO is very similar to that of the type I extradiol dioxygenases (cf.…”
Section: Gentisate 12-dioxygenase and Related Enzymesmentioning
confidence: 99%
“…The side chains of Arg127, His162 and Arg83 undergo significant displacement from their original positions, as seen in the substrate adduct structures of wild-type SDO. Accordingly, the same conformational changes caused by the movement of Arg83 towards the gentisate molecule were observed: closure of the loop corresponding to residues 75-85, which restricts access to the cavity, follwed by stabilization of loop [192][193][194][195][196][197][198] and the N-terminal region (residues [5][6][7][8][9][10][11][12][13][14]. These results demonstrated that replacement of a glycine residue by a slightly larger alanine residue did not alter the protein structure significantly, especially as this glycine residue is not involved in substrate binding or catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed the high activity of P34O against 2,4-, 2,5-and 3,5-dihydroxybenzoate, substrates which did not have hydroxyl groups in ortho configuration. Typically, the aromatic ring without ortho diol groups is cleaved by gentisate dioxygenase [Chen et al, 2008]. However, the activity of this enzyme was excluded in strain KB2 as it was not able to grow on gentisic acid as a substrate [unpubl.…”
Section: Substrate Specificity Of P34omentioning
confidence: 99%